Peningkatan Kemampuan Keaksaraan Awal Menggunakan Media Roda Pintar Di Paud Kasih Ibu - Eli Daryati; Mimpira Haryono; Rohayu Fadilla (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the low early literacy skills of children at PAUD Kasih Ibu, particularly regarding recognizing letter symbols, articulating letter sounds, and matching letters with images. The study aimed to enhance children's early literacy skills through the use of the